Dance and the corporeal uncanny - Rothfield, Philipa, author.
1 online resource
Keywords: Dance and the Corporeal Uncanny takes the philosophy of the body into the field of dance, through the lens of subjectivity and via its critique. It draws on dance and performance as its dedicated field of practice to articulate a philosophy of agency and movement. It is organized around two conceptual paradigms -one phenomenological (via Merleau-Ponty), the other an interpretation of Nietzschean philosophy, mediated through the work of Deleuze. The book draws on dance studies, cultural critique, ethnography and postcolonial theory, seeking an interdisciplinary audience in philosophy, dance and cultural studies.